Proceedings of the Florida and Interregional Conference on Sea Turtles, 24-25 July 1976, Jensen Beach, Florida. - Henderson, G.E. (ed.). (St.Petersburg, Florida Florida Dept. of Natural Resources, Marine Research Laboratory, 1978)
Florida Marine Research Publications no. 33
Keywords: Sea turtles